Personal and Collective Efficacy Beliefs Scales to Educators: Evidences of Validity - Casanova,Daniela Couto Guerreiro (2015)
Abstract This paper presents the Teacher Self-efficacy Scale, short version, and the School Collective Beliefs Scale adaptation and search of validities evidences process. After the semantic-cultural adaptation process, this study was composed by 380 educators from the public educational system in the state of São Paulo. The teacher self-efficacy scale, composed by 12 items, was organized into three factors. The School Collective Efficacy scale, composed by 12 items, was structured into two factors. Such adaptations, through the exploratory factor analysis yielded similar factor structure to the original scales, showed good evidence for variance explained, and internal consistency. Convergent validity was verified by the significant correlation between self-efficacy and collective efficacy. Criteria validity was verified through significant correlations between these beliefs and school performance. It is suggested to increase the sample size to confirm these results.